"I always tell my children to learn from me": Parental engagement in social and emotional learning in Malawi. (2022) - Lee, Jeongmin
Abstract: Parental involvement is increasingly becoming an integral part of children's education globally. This article presents parents' beliefs and strategies to contextualize relevant discourse in social and emotional learning (SEL) in Malawi. I interviewed 21 parents of primary school-aged children discussing (a) issues affecting children socially and emotionally, (b) parents' role in supporting SEL, and (c) strategies used in the process. This revealed various parental knowledge and strategies of SEL in the homes as well as socio-cultural networks and resources in the communities that complemented within-family SEL. Policy implications for the creation of system-wide SEL beyond school settings are discussed.